PerPot : A Metamodel for Simulation of Load Performance - Perl, J. (European Journal of Sport Science, 2001)
A metamodel "PerPot" for modeling phenomena of physiological adaptation is introduced. The PerPot software allows to analyze and optimize the interaction of load and performance. By use of Genetic Algorithms training plans can be generated or improved. siehe auch: https://www.semanticscholar.org/paper/PerPot-%3A-A-Metamodel-for-Simulation-of-Load-Perl/